Physics and astrophysics : a selection of key problems - Ginzburg, V. L. (Vitalii Lazarevich), 1916-2009 (Pergamon international library of science, technology, engineering, and social studies., 1985)
Physics and Astrophysics discusses some major problems concerned with macrophysics. Such topics as the controlled thermonuclear fusion, high- temperature superconductivity, and metallic exciton liquid in semiconductors are covered. The definition and elements related to microphysics are discussed. This section focuses on mass spectrum, quarks and gluons, and the interaction of particles at high and super high energies. The book gives a brief overview of the general theory of relativity. The production and origin of gravitational waves are discussed in detail. Cosmology is the study of space an.